Effects of dietary protein level on intake, digestibility, and energy expenditure in dairy heifers - Araújo, Laylles Costa; Valente, Eriton Egidio Lisboa; Filipini, Valdir da Trindade; Carvalho, Silvana Teixeira; Stahlhofer, Mariane; Cabral, Carla Heloisa Avelino; Damasceno, Matheus Leonardi; Barbizan, Mariana (Semina: Ciências Agrárias, 2020)
Balancing diets for protein affects both protein and energy use efficiency in cattle. This study aimed to evaluate the effects of dietary protein level on intake, digestibility and energy expenditure in Holstein heifers. Four Holstein heifers with a mean BW of 266.5 Â± 10.7 kg were distributed in a 4 x 4 balanced Latin square design. Each period was comprised of 14 d for adaptation and 6 d for samplings. The heifers were fed diets with 9, 12, 15 and 18% of crude protein (CP). Total feces and urine were collected. Rumen fluid was collected at 2, 4, 6 and 8 h after feeding. The energy expenditure was evaluated at 6 a.m., 12 a.m., 6 p.m. and 12 p.m. by a closed-circuit mask technique. The intake of dry matter (DM), organic matter (OM) and neutral detergent fiber (NDF) were similar between treatments (P > 0.05). Although the NDF digestibility was not changed (P > 0.05), the digestibilities of DM, OM, CP, non-fibrous carbohydrates, and total digestible nutrients increased linearly (P < 0.05) with increasing CP levels in the diet. Urinary urea nitrogen excretion and nitrogen retained increased linearly (P < 0.01) with increasing CP levels. Dietary CP levels did not affect (P =0.53) energy expenditure in heifers. Ruminal ammonia-nitrogen concentration peaked at 2-4 h after feeding. Increasing dietary CP levels from 9 to 18% does not affect feed intake and energy expenditure in heifers. However, it improves the digestibility of OM and nitrogen retention.